The Effect Of Service Quality And Price On Satisfaction Mediated By Priority Customer Purchasing Decisions At Permata Bank Jewel South Jakarta Branch - Monica Audina Setiawan; Herry Winoto; Saparso Saparso (Maneggio, 2024)
This study investigates the influence of service quality, price, and purchasing decisions on customer satisfaction. The findings indicate that service quality positively impacts customer satisfaction, with improvements in service quality leading to higher customer satisfaction. Similarly, price has a positive effect on customer satisfaction, where appropriate pricing strategies enhance customer satisfaction. Additionally, purchasing decisions are shown to positively influence customer satisfaction, suggesting that effective purchasing decisions increase customer satisfaction. The research further reveals that service quality positively affects purchasing decisions, indicating that better service quality encourages favorable purchasing decisions. Price also demonstrates a positive effect on customer satisfaction, reinforcing the importance of strategic pricing. Moreover, the study highlights the mediating role of purchasing decisions in the relationship between service quality and customer satisfaction, as well as between price and customer satisfaction. In summary, the study concludes that enhancing service quality and adopting strategic pricing can significantly improve customer satisfaction, with purchasing decisions serving as a key mediating factor in these relationships.